2008
DOI: 10.1097/mlg.0b013e318172c82c
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume as a Prognostic Factor in Oropharyngeal Squamous Cell Carcinoma Treated With Primary Radiotherapy

Abstract: Tumor volume does not appear to play a significant role in predicting locoregional recurrence for patients with primary squamous cell cancer of the oropharynx treated with primary radiotherapy. However, T4 status was predictive of poor locoregional control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Been et al . (12) showed no significant correlation of tumor volume with LRC ( p = 0.6244). Mendenhall et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Been et al . (12) showed no significant correlation of tumor volume with LRC ( p = 0.6244). Mendenhall et al .…”
Section: Discussionmentioning
confidence: 90%
“…Several earlier studies using primarily two-dimensional (2D) treatments modalities have observed no significant correlation between tumor volume and locoregional control (4, 10–12). In contrast, one 3D-CRT study (13) and two IMRT studies have shown that tumor volume is predictive of locoregional control but are limited by sample size or a large number of postoperative patients (14, 15).…”
Section: Introductionmentioning
confidence: 97%
“…Tumor burden is a known predictor of the response to definitive RT (28,29). The T stage represents the primary tumor burden; however, it is not a statistically significant prognostic factor for the PFS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that the volume of the primary tumor correlates with treatment outcome in patients with advanced HNSCC with the exception of oropharyngeal tumors. 40,41 However, it is unclear whether nodal volume predicts survival in patients with head and neck cancers. While some studies suggested deteriorating regional control 42,43 and worse disease-specific survival 44 in patients with large nodes, other studies did not find any relationship between nodal volume and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%